2014
DOI: 10.1080/19768354.2014.983969
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine, α2-adrenoceptor agonist, does not induce apoptosis in the brachial plexus of rats

Abstract: Dexmedetomidine (Precedex) is a selective α 2 -adrenoceptor agonist that shows opioid-sparing effects with reduced inhalational anesthetic requirement. Since the possibility that dexmedetomidine could induce nerve degeneration has not been completely ruled out, we evaluated whether it can induce apoptosis in rats when used in a nerve block. We performed hematoxylin and eosin staining, terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) assays, immunohistochemistry for caspase-3 and ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 36 publications
(39 reference statements)
0
16
0
Order By: Relevance
“…Such endothelial dysfunction is present in cases of erectile dysfunction [ 29 ]. Activation or upregulation of receptors is strongly implicated in the therapeutic strategy for many diseases [ 30 , 31 ]. Leoni et al [ 29 ] suggested the role of physical exercise in the modulation of endothelial function and its implications on erectile function.…”
Section: Discussionmentioning
confidence: 99%
“…Such endothelial dysfunction is present in cases of erectile dysfunction [ 29 ]. Activation or upregulation of receptors is strongly implicated in the therapeutic strategy for many diseases [ 30 , 31 ]. Leoni et al [ 29 ] suggested the role of physical exercise in the modulation of endothelial function and its implications on erectile function.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that tamsulosin exerted a neuroprotective effect on intracerebral hemorrhage by inhibiting hippocampal cell apoptosis via α 1 -adrenoceptor blockade [ 15 ]. During the apoptotic process, the number of TUNEL-positive cells increases [ 22 ], whereas an unchanged number of TUNEL-positive cells indicates that apoptosis did not occur [ 32 ]. In the present study, the number of TUNEL-positive cells in the hippocampus did not change following tamsulosin treatment ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the previous study, dexmedetomidine did not induce apoptosis in the brachial plexus of rats (39). The present study also revealed that dexmedetomidine did not exert any effects on the apoptosis-related molecules under the normal (Sham operation) conditions.…”
Section: Discussionmentioning
confidence: 70%